The effect of the step frequency manipulation on the step length in competitive race walkers - Vando, S.; Padulo, J. (Sport Sciences for Health, 2012)
The present study investigated the effects of step frequency manipulation during training in slopes (2%) on biomechanical parameters at Iso-Efficiency Speed (IES). Twelve male race walkers were randomly allocated to one of two training groups for three weeks: step frequency manipulation group (RWM, n=6) and free step frequency group (RWF, n=6). The RWM performed with 5 sets of 5 minutes race walking 2% slope at IES with a manipulated step frequency (calculated in order to replicate the same step length elicited during level) while in RWM the step frequency was freely chosen. ANOVA with repeated measures and Bonferroni post hoc showed significant differences between both training groups F(1,10)= 32.856, p < 0.0001 (2= 0.767) respect to baseline condition. In RWM group showed a increased step length 4.54% (p < 0.0001), contact time 4.58% (p < 0.001) and decreased step frequency 4.44% (p < 0.0001). Conversely, in RWF the effect of the training has showed a decreased in step length 1.18% (p < 0.0001), contact time <1% (p < 0.0001) and increased step frequency 1.19% (p < 0.0001). These findings coincide with characteristics of better race walking performances. The results from the study could help coaches to device training methods which could improve an athlete`s performance through increasing step length. The method provided may aid faster race times for athlete`s.